2001
DOI: 10.1086/322653
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Blind, Double‐Dummy, Multicenter Trial of Voriconazole and Fluconazole in the Treatment of Esophageal Candidiasis in Immunocompromised Patients

Abstract: The efficacy, safety, and tolerability of voriconazole and fluconazole were compared in 391 immunocompromised patients with mycology- and biopsy-proven esophageal candidiasis. Primary efficacy analysis (256 patients) of esophageal treatment as assessed by esophagoscopy revealed success rates of 98.3% with voriconazole and 95.1% with fluconazole. The 95% confidence interval for the difference in success rates ranged from -1.0% to 7.5%. The overall safety and tolerability of both antifungals were acceptable. Few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
2
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(157 citation statements)
references
References 30 publications
3
144
2
8
Order By: Relevance
“…Literatürde karşılaştırmalı çalışmalarda hem etkinlik hem de tolere edilebilirlik açısından flukonazol ve vorikonazol benzer sonuçlar sergilemişlerdir [20][21][22] . Ancak özellikle hematolojik maligniteli hastalarda C. krusei 'de intrensenk flukonazol direncinin bulunması ve başta C. glabrata olmak üzere çeşitli Candida suşlarında flukonazole direnç saptanması, albicans dışı Candida türlerindeki sıklığın son yıllarda artışı, flukonazolun aspergillus gibi küf mantarlarına etkisiz olması göz önünde bulundurulduğunda, bu hasta grubu için mukozal kandida enfeksiyonlarının empirik tedavisinde vorikonazol daha iyi bir alternatif olabilir.…”
Section: Discussionunclassified
“…Literatürde karşılaştırmalı çalışmalarda hem etkinlik hem de tolere edilebilirlik açısından flukonazol ve vorikonazol benzer sonuçlar sergilemişlerdir [20][21][22] . Ancak özellikle hematolojik maligniteli hastalarda C. krusei 'de intrensenk flukonazol direncinin bulunması ve başta C. glabrata olmak üzere çeşitli Candida suşlarında flukonazole direnç saptanması, albicans dışı Candida türlerindeki sıklığın son yıllarda artışı, flukonazolun aspergillus gibi küf mantarlarına etkisiz olması göz önünde bulundurulduğunda, bu hasta grubu için mukozal kandida enfeksiyonlarının empirik tedavisinde vorikonazol daha iyi bir alternatif olabilir.…”
Section: Discussionunclassified
“…The largest prospective clinical trial of voriconazole as primary therapy for invasive aspergillosis in adults showed better clinical response and improved survival in subjects receiving voriconazole versus those receiving amphotericin B deoxycholate [104]. A multicenter trial of voriconazole versus fluconazole in treating esophageal candidiasis in 391 immunocompromised patients showed similar success rates with voriconazole (98.3%) and fluconazole (95.1%) [105]. While overall safety and tolerability of both antifungals was acceptable in this study, fewer patients discontinued voriconazole than fluconazole due to poor clinical response, but more patients discontinued voriconazole because of laboratory abnormalities or adverse events.…”
Section: Clinical Studies In Adultsmentioning
confidence: 99%
“…The first, a non-inferiority study, enrolled 391 immunocompromised adult patients with esophageal candidiasis, who were randomly assigned to receive either voriconazole or fluconazole as oral therapy. 44 On the basis of a per-protocol population analysis at the end of therapy, oral voriconazole was non-inferior to fluconazole in terms of treatment success rate (defined as patients with cure or improvement, as determined by esophagoscopy). 44 The second study, a randomized, multicentre, nonblinded, non-inferiority trial, compared voriconazole with amphotericin B for the treatment of invasive candidiasis in 422 nonneutropenic patients.…”
Section: Candidiasismentioning
confidence: 99%
“…44 On the basis of a per-protocol population analysis at the end of therapy, oral voriconazole was non-inferior to fluconazole in terms of treatment success rate (defined as patients with cure or improvement, as determined by esophagoscopy). 44 The second study, a randomized, multicentre, nonblinded, non-inferiority trial, compared voriconazole with amphotericin B for the treatment of invasive candidiasis in 422 nonneutropenic patients. 45 A modified intention-to-treat analysis showed no significant difference between the 2 groups in terms of the primary end point for efficacy, success rate at 12 weeks after the end of therapy.…”
Section: Candidiasismentioning
confidence: 99%